Mapping migration habitat for western monarch butterflies reveals need for public-private approach to conservation - McIntyre, Patrick J.; Ceasar, Hannah; Young, Bruce E. (Frontiers in Ecology and Evolution, 2024)
IntroductionIdentifying habitat of migratory species to effectively support conservation and management requires careful consideration of (1) the data used to inform habitat models, (2) the biology of the organism, (3) land tenure, and (4) the needs of the target audience.MethodsTo provide this information for western U.S. monarch butterflies, a population undergoing decline, we modeled habitat during the spring and fall migrations. Our approach controlled for biases in citizen science locality data, the principal source of monarch observation data, and incorporated needs for milkweed host plants in the spring and nectar plants in the fall.Results and DiscussionThe results showed the distribution of habitat for spring and fall migration, where the Coast Range and Central Valley in California and riparian areas throughout the range were particularly important. Just 29% of predicted habitat for spring and fall migrations, combined, overlapped between the two seasons. Although the U.S. federal government manages 53% of the land in the western U.S., government land makes up just 11.7% of the spring migration range and 23.5% of the fall migration range. State and local governments and non-governmental organizations (NGOs) manage an additional 4.2% of the spring and 4.0% of the fall migration habitat. Thus, like eastern monarchs, western monarchs rely heavily on land under private ownership for their migration and to be successful, monarch conservation efforts must embrace a public-private approach. Among federal agencies, the Bureau of Land Management (BLM; 5.9% of spring and 9.7% of fall habitat) and Forest Service (3.3% of spring and 9.2% of fall habitat) manage the greatest shares. Less than half of the government and NGO owned habitat for both migrations is managed for biodiversity conservation rather than multiple uses (spring, 46.0%; fall, 36.5%). We created custom model outputs for the BLM to highlight areas of both regional and local importance for migrating monarchs in each BLM administrative unit, enabling managers across the agency to contribute to recovery. The outcomes provide input at a relevant spatial scale to support actions such as habitat restoration, riparian zone protection, and pesticide use reduction to enhance conditions for migrating monarchs on both government and private lands.